2022
DOI: 10.3390/ijms23136915
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Matrix Cues on Intervertebral Disc Development, Degeneration, and Regeneration

Abstract: Back pain is one of the leading causes of disability worldwide and is frequently caused by degeneration of the intervertebral discs. The discs’ development, homeostasis, and degeneration are driven by a complex series of biochemical and physical extracellular matrix cues produced by and transmitted to native cells. Thus, understanding the roles of different cues is essential for designing effective cellular and regenerative therapies. Omics technologies have helped identify many new matrix cues; however, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 306 publications
0
12
0
Order By: Relevance
“…Based on the evidences here obtained, it will be necessary components and mechanical properties of the ECM of the discal tissue vary depending on the anatomical site within the spine. 6 The future direction is precisely to develop personalized biomaterials tailored to match the unique signature of ECM associated to the different IDD subtypes (disc fibrosis, disc calcification and disc herniations) to halt disease progression, promote tissue regeneration, and relieve the symptom, that is, discogenic low back pain. 49 We would like to conclude that, considering their versatility, the WJMs proposed here are also good candidates for the treatment of degenerative joint diseases such as osteoarthritis or various traumas that can affect the joints.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the evidences here obtained, it will be necessary components and mechanical properties of the ECM of the discal tissue vary depending on the anatomical site within the spine. 6 The future direction is precisely to develop personalized biomaterials tailored to match the unique signature of ECM associated to the different IDD subtypes (disc fibrosis, disc calcification and disc herniations) to halt disease progression, promote tissue regeneration, and relieve the symptom, that is, discogenic low back pain. 49 We would like to conclude that, considering their versatility, the WJMs proposed here are also good candidates for the treatment of degenerative joint diseases such as osteoarthritis or various traumas that can affect the joints.…”
Section: Discussionmentioning
confidence: 99%
“…The values are within the range for the non-degenerate human NP reported in previous studies. 31,32 Together, the resulting NP glue is bioadhesive, injectable, and viscoelastic.…”
Section: Design Principles Of Ivd-mimetic Hybrid Bioadhesivesmentioning
confidence: 99%
“…Indeed, the dysregulation of ECM anabolism and catabolism, and the absence of crucial components, such as proteoglycans and type II collagen, are typical pathological changes in IDD. Matrix metalloproteinases (MMPs), and a disintegrin and metalloproteinase with thrombospondin motifs (ADAMTSs), are two families of enzymes that regulate the ECM ( Kibble et al, 2022 ). Inflammatory factors not only accelerate the catabolism of key substances, but also downregulate their source synthesis and expression.…”
Section: Relationships Between Inflammation and Iddmentioning
confidence: 99%
“…In addition to IL-1β, Séguin et al ( Séguin et al, 2005 ) also reported that TNF-α increased the expression levels of MMP-1, -3, -13, ADAMTS-4, and -5, and reduced the expression of type II collagen and proteoglycan genes in NP cells. The development of proteomics and transcriptomics is expected to reveal more detailed changes in the expression and synthesis of substances at the spatiotemporal level ( Eckersley et al, 2021 ; Kibble et al, 2022 ). Overall, the close relationship between inflammation and other mechanisms further indicates that controlling inflammation has great potential for the treatment of IDD.…”
Section: Relationships Between Inflammation and Iddmentioning
confidence: 99%